A method for determining lithium content in polymetallic ore by sulfuric acid-hydrofluoric acid decomposition-boric acid complexing-splitting method

By combining sulfuric acid-hydrofluoric acid decomposition and boric acid complexation with a small-volume fractionation method, the problem of low lithium content determination results in polymetallic ores was solved, and high-accuracy lithium analysis was achieved.

CN122330028APending Publication Date: 2026-07-03SICHUAN XIYE GEOLOGY TESTING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610783431.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-02
Publication Date
2026-07-03

Smart Images

  • Figure SMS_6
    Figure SMS_6
  • Figure SMS_7
    Figure SMS_7
  • Figure SMS_8
    Figure SMS_8
Patent Text Reader

Abstract

This invention discloses a method for determining lithium content in polymetallic ores using a sulfuric acid-hydrofluoric acid decomposition-boric acid complexation-split method, belonging to the field of lithium ore analysis and testing technology. The method first completely decomposes the sample using a mixed acid solution of sulfuric acid and hydrofluoric acid. Then, excess boric acid is added and the sample is treated with micro-heating to eliminate free HF. The solution is then diluted to a final volume to obtain a mother liquor, which is then split and diluted to prepare the test solution. Finally, the lithium content is determined using an atomic absorption spectrophotometer. Results show that this method effectively inhibits the slow hydrolysis of P, Al, Sn, Nb, and Ta, as well as the adsorption of lithium by colloids, significantly improving the accuracy and repeatability of lithium content determination. This method solves the technical problems of interference from fluoride ions, lithium adsorption due to metal ion hydrolysis, low detection results, and poor recovery rates in traditional methods, and is suitable for routine lithium analysis in high-P-Al-Sn-Nb-Ta samples.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium ore analysis and testing technology, specifically relating to a method for determining the lithium content in polymetallic ores using a sulfuric acid-hydrofluoric acid decomposition-boric acid complexation-splitting method. Background Technology

[0002] As the application of lithium in new energy materials and functional alloys continues to expand, accurate analysis of lithium resources and associated elements is becoming increasingly important. In polymetallic ores and metallurgical intermediates, lithium often occurs in association with high field strength elements such as tin, niobium, and tantalum, while also containing high levels of phosphorus and aluminum.

[0003] In the analysis of these complex mineral samples, hydrofluoric acid (HF) is usually required for decomposition to destroy the silicate and Nb-Ta phase structures. However, the resulting high fluoride and high matrix system adversely affects subsequent lithium determination: on the one hand, residual HF affects the nebulization process and instrument stability; on the other hand, in solutions with high P, Al, Sn, Nb, and Ta contents, even under acidic conditions, Sn... 4+ 、Nb 5+ and Ta 5+ Slow hydrolysis and polymerization may still occur, generating colloids such as SnO2·xH2O, Nb2O5·xH2O, and Ta2O5·xH2O, which may affect the alkali metal ions Li. + Significant physical adsorption and encapsulation occur, leading to a systematic underestimation of the measured values.

[0004] Traditional methods involve directly diluting the decomposition solution in large volumes, which leads to a rapid decrease in acidity during dilution. This promotes the hydrolysis and polymerization of high-field-strength ions, causing turbidity to easily appear during sample storage. Spike recoveries are only about 77-79%, which cannot meet the accurate analytical requirements of complex matrix samples. Therefore, developing an analytical method that can effectively eliminate HF interference and suppress lithium adsorption by multi-element hydrolysate colloids has significant practical value. Summary of the Invention

[0005] In view of the above-mentioned prior art, the present invention discloses a method for determining the lithium content in polymetallic ores by sulfuric acid-hydrofluoric acid decomposition-boric acid complexation-splitting method, so as to solve the technical problem of low lithium content determination results in high P-Al-Sn-Nb-Ta samples in the prior art.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for determining the lithium content in polymetallic ores using a sulfuric acid-hydrofluoric acid decomposition-boric acid complexation-separation method is provided, comprising the following steps: Sample pretreatment: Place the ore sample in a container and add a mixture of sulfuric acid and hydrofluoric acid. Heat the sample to decompose it. Then add boric acid to the decomposition solution and heat at 60-80℃ for 5-10 minutes. After making up the volume, obtain the mother liquor. Take a portion of the mother liquor and dilute it with a sulfuric acid solution containing tartaric acid to obtain the test solution. The mass-volume concentration of tartaric acid in the sulfuric acid solution is 0.25-0.35%, and the volume concentration of sulfuric acid is 1.8-2.2%. Preparation of standard solutions: Prepare lithium standard working curve solutions with the same acidity and matrix as the test solution; Determination: The lithium content in the test solution and the lithium standard working curve solution was determined by atomic absorption spectrophotometer, and the lithium content in the ore was calculated.

[0007] Based on the above technical solution, the present invention can be further improved as follows: Furthermore, the ore sample contains at least one of the following elements in addition to lithium: phosphorus, aluminum, tin, niobium, and tantalum.

[0008] Furthermore, the volume ratio of sulfuric acid to hydrofluoric acid in the sulfuric acid-hydrofluoric acid mixture is 1:8~10, preferably 1:9; the material-liquid ratio of the ore sample to the sulfuric acid-hydrofluoric acid mixture is 0.09~0.10:10mL.

[0009] Furthermore, the decomposition temperature is 200~300℃.

[0010] Furthermore, the ratio of sulfuric acid-hydrofluoric acid mixture to boric acid is 10mL:4~5g, preferably 10mL:4.5g.

[0011] Furthermore, the volume ratio of the mother liquor to the sulfuric acid solution is 1:49.

[0012] Furthermore, the tartaric acid concentration in the sulfuric acid solution is 0.3% by mass and the sulfuric acid concentration is 2% by volume.

[0013] Furthermore, the operating parameters of the atomic absorption spectrophotometer include: measurement time of 1.5~5s, air flow rate of 12~14L / min, acetylene flow rate of 1.50~2.50L / min, and burner head height of 10.0~15.0mm.

[0014] Furthermore, the lithium content is calculated using the following formula: , in To determine the lithium concentration in the solution, For the final constant volume, To divide the volume, V 0 represents the volume of the mother liquor. denoted as the sample mass, and 2.1527 as the coefficient for the conversion of lithium to lithium oxide.

[0015] The beneficial effects of this invention are: This invention establishes a method suitable for determining the lithium content in high P-Al-Sn-Nb-Ta samples. By eliminating HF interference through boric acid complexation and combining it with a small-volume splitting strategy, the hydrolysis and colloid formation of Sn, Nb, and Ta are effectively suppressed, thereby reducing lithium adsorption loss and improving the recovery rate. This method is simple to operate, provides reliable results, and can be used for routine lithium analysis in complex multimetallic systems. Detailed Implementation

[0016] The specific embodiments of the present invention will be described in detail below with reference to examples.

[0017] Instrument: Atomic absorption spectrophotometer (model: 240FSAA).

[0018] Reagents: hydrofluoric acid (ρ=1.15g / mL, Chengdu Jinshan Chemical Reagent Co., Ltd.), sulfuric acid (ρ=1.84g / mL, Chengdu Jinshan Chemical Reagent Co., Ltd.), boric acid (analytical grade, Chengdu Jinshan Chemical Reagent Co., Ltd.), tartaric acid (analytical grade, Chengdu Jinshan Chemical Reagent Co., Ltd.), deionized water (conductivity: 4.76μs / cm).

[0019] Sample: GBW07184 is a national first-class standard material; the raw ore sample is mainly composed of spodumene and phosphogypsum; the raw ore sample was subjected to spectral semi-quantitative analysis, and the results are shown in Table 1.

[0020] Table 1. Semi-quantitative results of the spectrum (mass fraction, %)

[0021] Example 1 (Small volume split + 0.3% (w / v) tartaric acid in 2% (v / v) sulfuric acid solution) A method for determining the lithium content in polymetallic ores, comprising the following steps: Pretreatment: Weigh 0.1g of raw ore sample (accurate to 0.0001g) and place it in a PTFE digestion container. Wet the container with 1mL of water, then add 10mL of a sulfuric acid-hydrofluoric acid mixture (volume ratio 1:9). Heat the sample at 220℃ until complete decomposition or no obvious solid residue remains. Cool to room temperature. Add boric acid to the decomposition solution (the ratio of sulfuric acid-hydrofluoric acid mixture to boric acid is 10mL:4.5g). Heat at 70℃ for 8 minutes, adding boric acid as needed until excess boric acid precipitates in the solution, ensuring complete complexation of free HF. After cooling, transfer the solution to a 10mL plastic volumetric flask and dilute to volume, obtaining the mother liquor. Immediately and accurately pipette 1.00mL of the mother liquor into a 50mL volumetric flask, dilute to the mark with a 2% (v / v) sulfuric acid solution containing 0.3% (w / v) tartaric acid, and shake well to obtain the test solution.

[0022] Standard solutions: Lithium (Li) solution GSB04-1734-2004 from the National Center for Analysis and Testing of Nonferrous Metals and Electronic Materials was used as the standard stock solution. The solution was diluted twice to prepare working curves with lithium (Li) concentrations of 0.00 mg / L, 1.00 mg / L, 3.00 mg / L, 5.00 mg / L, 10.0 mg / L, and 15.0 mg / L. The acidity and matrix of the standard solution were kept consistent with those of the sample digestion solution.

[0023] Spiked recovery experiment: Take samples 1 and 2 separately and use the same sample pretreatment method. The difference is that after weighing the sample into the PTFE digestion container, use a 2mL graduated pipette to accurately transfer 1mL of 1.00mg / mL lithium standard solution into the PTFE digestion container and then moisten it with water. The rest of the steps are the same.

[0024] Determination: The lithium content was then tested using an atomic absorption spectrophotometer. The instrument operating parameters are shown in Table 2.

[0025] Table 2

[0026] The mass fraction of lithium is calculated using the following formula:

[0027] in To determine the lithium concentration (mg / L) in the solution. This is the final volume (mL). To measure the volume (mL). V 0 represents the volume of the mother liquor (mL). denoted as sample mass (g), and 2.1527 as the coefficient for lithium conversion to lithium oxide. The test results are shown in Table 3.

[0028] Table 3

[0029] Comparative Example 1 (no splitting, no boric acid, no tartaric acid) A method for determining the lithium content in polymetallic ores, comprising the following steps: Pretreatment: Weigh 0.1g of raw ore sample (accurate to 0.0001g) into a PTFE digestion container, moisten with 1mL of water, add 15mL of hydrofluoric acid and 2mL of (1+1) sulfuric acid (concentrated sulfuric acid), slowly add to an equal volume of deionized water, mix well, and cool to obtain the solution; heat at 220℃ to decompose the sample until it is completely decomposed, then heat to evaporate until the sulfur trioxide white fumes are exhausted, remove and cool. Add 5mL of (1+1) sulfuric acid and 20mL of water, place on a hot plate to heat until the salts are completely dissolved, remove and cool to room temperature, transfer the solution to a 250mL volumetric flask, dilute with water to the mark, shake well, and let it clarify to obtain the test solution.

[0030] Standard solutions: Lithium (Li) solution GSB04-1734-2004 from the National Center for Analysis and Testing of Nonferrous Metals and Electronic Materials was used as the standard stock solution. The solution was diluted twice to prepare working curves with lithium (Li) concentrations of 0.00 mg / L, 1.00 mg / L, 3.00 mg / L, 5.00 mg / L, 10.0 mg / L, and 15.0 mg / L. The acidity and matrix of the standard solution were kept consistent with those of the sample digestion solution.

[0031] The testing method is the same as in Example 1, and the test results are shown in Table 4.

[0032] Table 4

[0033] Comparative Example 2 (small volume split + 0.3% (w / v) tartaric acid in 1% (v / v) sulfuric acid solution) A method for determining the lithium content in polymetallic ores, comprising the following steps: Pretreatment: Weigh 0.1g of raw ore sample (accurate to 0.0001g) and place it in a PTFE digestion container. Wet the container with 1mL of water, then add 10mL of a sulfuric acid-hydrofluoric acid mixture (volume ratio 1:9). Heat the sample at 220℃ until complete decomposition or no obvious solid residue remains. Cool to room temperature. Add boric acid to the decomposition solution (hydrofluoric acid to boric acid ratio 1mL:0.5g). Heat at 70℃ for 8 minutes, adding boric acid as needed until excess boric acid precipitates in the solution, ensuring complete complexation of free HF. After cooling, transfer the solution to a 10mL plastic volumetric flask and dilute to volume, obtaining the mother liquor. Immediately and accurately pipette 1.00mL of the mother liquor into a 50mL volumetric flask and dilute to the mark with a 1% (v / v) sulfuric acid solution containing 0.3% (w / v) tartaric acid. Dilute to the mark and mix well to obtain the test solution.

[0034] Standard solutions: Lithium (Li) solution GSB04-1734-2004 from the National Center for Analysis and Testing of Nonferrous Metals and Electronic Materials was used as the standard stock solution. The solution was diluted twice to prepare working curves with lithium (Li) concentrations of 0.00 mg / L, 1.00 mg / L, 3.00 mg / L, 5.00 mg / L, 10.0 mg / L, and 15.0 mg / L. The acidity and matrix of the standard solution were kept consistent with those of the sample digestion solution.

[0035] The testing method is the same as in Example 1, and the test results are shown in Table 5.

[0036] Table 5

[0037] Comparative Example 3 (small volume split + 2% (v / v) sulfuric acid) A method for determining the lithium content in polymetallic ores, comprising the following steps: Pretreatment: Weigh 0.1g of raw ore sample (accurate to 0.0001g) and place it in a PTFE digestion container. Wet the container with 1mL of water, then add 10mL of a sulfuric acid-hydrofluoric acid mixture (volume ratio 1:9). Heat the sample at 220℃ until completely decomposed or with no obvious solid residue. Cool to room temperature. Add boric acid to the decomposition solution (hydrofluoric acid to boric acid ratio of 1mL:0.5g). Heat at 70℃ for 8 minutes, adding boric acid as needed until excess boric acid precipitates in the solution, ensuring complete complexation of free HF. After cooling, transfer the solution to a 10mL plastic volumetric flask and dilute to volume, obtaining the mother liquor. Immediately and accurately pipette 1.00mL of the mother liquor into a 50mL volumetric flask, dilute to the mark with 2% (v / v) sulfuric acid solution, and shake well to obtain the test solution.

[0038] Standard solutions: Lithium (Li) solution GSB04-1734-2004 from the National Center for Analysis and Testing of Nonferrous Metals and Electronic Materials was used as the standard stock solution. The solution was diluted twice to prepare working curves with lithium (Li) concentrations of 0.00 mg / L, 1.00 mg / L, 3.00 mg / L, 5.00 mg / L, 10.0 mg / L, and 15.0 mg / L. The acidity and matrix of the standard solution were kept consistent with those of the sample digestion solution.

[0039] The testing method is the same as in Example 1, and the test results are shown in Table 6.

[0040] Table 6

[0041] As can be seen from the measurement results in the examples and comparative examples, under non-split conditions, after sample decomposition, direct large-volume volume adjustment resulted in rapid dilution of the system, Sn. 4+ 、Nb 5+ Ta 5+Hydrolysis and polymerization occur during the decrease in acidity, generating SnO2·XH2O, Nb2O5·XH2O, and Ta2O5·XH2O colloids, which are beneficial to Li. + Significant adsorption and encapsulation occur, leading to lower measured values ​​and lower recovery rates. Using small-volume splitting effectively avoids the influence of hydrolysis and adsorption. Low acidity is insufficient to inhibit the hydrolysis of Nb, Ta, and Sn; even with the addition of tartaric acid, the system cannot be completely stabilized. Experiments show that simply increasing acidity after splitting or adding tartaric acid at low acidity is insufficient to solve the problem; both must work together to significantly improve the recovery rate. For repeated determinations in high-P-Al-Sn-Nb-Ta samples, a triple approach of high acidity, large-multiplier splitting, and tartaric acid complexation is necessary to prevent lithium from being implicitly adsorbed, resulting in severely low results. Using the determination method of this invention, the relative standard deviation (RSD) of lithium in the national primary standard material GBW07184 is less than 5%, and the spiked recovery rate is between 95% and 105%, indicating that the method has good accuracy.

[0042] The specific embodiments of the present invention have been described in detail, but should not be construed as limiting the scope of protection of this patent. Various modifications and variations that can be made by those skilled in the art without inventive effort within the scope described in the claims are still within the scope of protection of this patent.

Claims

1. A method for determining the lithium content in a polymetallic ore by the sulfuric acid-hydrofluoric acid decomposition-boric acid complexation-split flow method, characterized by, Includes the following steps: Sample pretreatment: Place the ore sample in a container and add a mixture of sulfuric acid and hydrofluoric acid. Heat the sample to decompose it. Then add boric acid to the decomposition solution and heat at 60-80℃ for 5-10 minutes. After making up the volume, obtain the mother liquor. Take a portion of the mother liquor and dilute it with a sulfuric acid solution containing tartaric acid to obtain the test solution. The mass-volume concentration of tartaric acid in the sulfuric acid solution is 0.25-0.35%, and the volume concentration of sulfuric acid is 1.8-2.2%. Preparation of standard solutions: Prepare lithium standard working curve solutions with the same acidity and matrix as the test solution; Determination: The lithium content in the test solution and the lithium standard working curve solution was determined by atomic absorption spectrophotometer, and the lithium content in the ore was calculated.

2. The determination method according to claim 1, characterized in that: In addition to lithium, the ore sample contains at least one of the following elements: phosphorus, aluminum, tin, niobium, and tantalum.

3. The determination method according to claim 1, characterized in that: The volume ratio of sulfuric acid to hydrofluoric acid in the sulfuric acid-hydrofluoric acid mixed acid is 1:8~10; the material-liquid ratio of ore sample to sulfuric acid-hydrofluoric acid mixed acid is 0.09~0.10:10mL.

4. The determination method according to claim 1, characterized in that: The decomposition temperature is 200~300℃.

5. The determination method according to claim 1, characterized in that: The ratio of sulfuric acid-hydrofluoric acid mixed acid to boric acid is 10 mL: 4~5 g.

6. The determination method according to claim 1, characterized in that: The volume ratio of the mother liquor to the sulfuric acid solution is 1:

49.

7. The determination method according to claim 1, characterized in that: The operating parameters of the atomic absorption spectrophotometer include: measurement time of 1.5~5s, air flow rate of 12~14L / min, acetylene flow rate of 1.50~2.50L / min, and burner head height of 10.0~15.0mm.

8. The determination method according to claim 1, characterized in that, The lithium content is calculated using the following formula: , in To determine the lithium concentration in the solution, For the final constant volume, To divide the volume, V 0 represents the volume of the mother liquor. denoted as the sample mass, and 2.1527 as the coefficient for the conversion of lithium to lithium oxide.